Analysis of maternity patients' satisfactory to maternity room installment in Dr. Soetomo Hospital Surabaya - M Reza Zulkarnain; Baksono Winardi (Universitas Airlangga, 2020)
Objectives: To analyze the maternity patient satisfaction for services provided in the maternity room of Dr Soetomo General Hospital Surabaya. Materials and Methods: Cross-sectional observational studies. In this study only made observation without intervention. The data used in this study was obtained using form of questionnaires, using Likert Scale. The data is processed by using program SPSS v20 and Microsoft Excell 2007 program Results: During October - December 2017, based on importance performance analysis patient satisfaction divided into 4 quadrant (quadran A,B,C and D), quadrant A is a top priority for service quality improvement. Percentage of performance level nurse or doctor willing to help patient is 52,4%. Percentage of performance level nurse or doctor to inform when the service will be given is 59,9%. Percentage of performance level to keep patient as top priority is 70,3%. Percentage of performance level to look carefully to asptient is 87%. Percentage of performance level to respond patient requet immediately is 90. Based on custumer satisfaction index (CSI) the index score of patient satisfaction is 74,3%, which is that value dexcribes the overall patient in the maternity installation is satisfied with the health service provided. Conclusion: Patient of maternity room at Dr. Soetomo General Hospital is generally satisfied with the current quality of service performace. The value of patient satisfaction showed a value of 74,53% which means almost 75% of patient expectations is fulfilled and the remaining about 25% still need improvement. The particular concern in improvement of service is desire to always help patient, provide information about the treatment, patient always to be top priority, and raising individual attention to the patient.